ebXML у розвитку ринку інформаційних послуг - Pleskach, V. L. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2019)
Application of the ebXML technology to business-processes unloading at enterprises is proposed, thanks to which industrialists can find each other in the electronic distributed environment Internet, collaborate together for definition of advantageous joint business-processes on-line, come to agreement on collaboration terms, and quickly implement necessary business-processes.